Association study of NR5A1 rs1110061 with infertile male in 401 Vietnamese individuals - Minh Duc, Bui; Lan Anh, Luong Thi; Van Hai, Nong; Thuy Duong, Nguyen (Vietnam Journal of Biotechnology, 2021)
Male infertility is a reproductive issue involving defects in the quantity and quality of sperm. Besides the exogenous elements such as harmful habits, pollution, genetic factors including disorders in a single gene, group of genes, or chromosomes, are the etiology causing infertility in men. NR5A1 is well-known as a candidate gene involved in male infertility, including 46, XY disorders of sex development (DSD), cryptorchidism, micropenis, spermatogenic failure, non-obstructive azoospermia, and oligozoospermia. This study aimed to identify the single nucleotide polymorphism (SNP) associated with male infertility in the NR5A1 gene in a Vietnamese cohort of 202 infertile men and 199 healthy controls. By directly sequencing the coding region of the NR5A1 gene in 56 cases and 21 controls, only one missense mutation c.437G>C (p.Gly146Ala; rs1110061) in exon 4 was found. The variant was detected in 34 patients, of which 27 were heterozygous (GC) and 7 were homozygous (CC). In the control group, 15 individuals carried this mutation, including 10 with heterozygous (GC) and 5 with homozygous (CC). To further investigate the association of the polymorphism NR5A1 rs11100061 with male infertility disease, we performed PCR-RFLP in 202 infertile and 199 healthy men to assess the genotypes and alleles. The results indicated that the distribution of the genotypes of the polymorphism was in accordance with Hardy-Weinberg equilibrium (p-values > 0.05). However, no association was detected between the polymorphism and male infertility (p-values > 0.05).